Disformal dark energy at colliders - Brax, Philippe; Burrage, Clare; Englert, Christoph (American Physical Society, 2015)
Disformally coupled, light scalar fields arise in many of the theories of dark energy and modified gravity that attempt to explain the accelerated expansion of the Universe. They have proved difficult to constrain with precision tests of gravity because they do not give rise to fifth forces around static nonrelativistic sources. However, because the scalar field couples derivatively to standard model matter, measurements at high-energy particle colliders offer an effective way to constrain and potentially detect a disformally coupled scalar field. Here we derive new constraints on the strength of the disformal coupling from LHC run 1 data and provide a forecast for the improvement of these constraints from run 2. We additionally comment on the running of disformal and standard model couplings in this scenario under the renormalization group flow.